2018
DOI: 10.1017/ice.2018.255
|View full text |Cite
|
Sign up to set email alerts
|

From ward to washer: The survival of Clostridium difficile spores on hospital bed sheets through a commercial UK NHS healthcare laundry process

Abstract: ObjectiveTo quantify the survival of Clostridium difficile spores on hospital bed sheets through the United Kingdom National Health System (UK NHS) healthcare laundry process (Health Technical Memorandum (HTM) 01-04) in vitro and on bed sheets from patients with C. difficile through the commercial laundry.MethodsClostridium difficile spores were inoculated onto cotton sheets and laundered through a simulated washer extractor cycle using an industrial bleach detergent with sodium hypochlorite 15% and peracetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 15 publications
2
49
0
2
Order By: Relevance
“…However, there are other possible explanations. First, given the retrospective nature of most studies, patients may have acquired the infection not in the niche of the genotype, as shown by Clostridioides difficile (Tarrant et al, 2018). Second, some genotypes may be more frequent and better adapted than others, persisting in hospital facilities for a longer time.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are other possible explanations. First, given the retrospective nature of most studies, patients may have acquired the infection not in the niche of the genotype, as shown by Clostridioides difficile (Tarrant et al, 2018). Second, some genotypes may be more frequent and better adapted than others, persisting in hospital facilities for a longer time.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, reusable healthcare textiles in close contact with patients for extended periods of time can become soiled with bodily fluids, blood and skin scales, leading to contamination with potential pathogens (Creamer & Humphreys, 2008). Pathogens linked to HCAIs have been shown to contaminate textiles in the clinical environment; 51 CFU/25 cm 2 C. difficile spores were recover from soiled hospital bed sheets of C. difficile infection patients (Tarrant, Jenkins & Laird, 2018) and 92% of privacy curtains are contaminated with at least one bacterial species within one week, including S. aureus (62% positive), MRSA (21% positive) and VRE (42% positive) (Ohl et al, 2012).…”
Section: Contamination Of Healthcare Textilesmentioning
confidence: 99%
“…Sizun, Yu & Talbot (2000) increases survival duration (Fijan, Pahor & Šostar Turk, 2017). Natural contamination levels of healthcare textiles are likely to be smaller, for example 50 CFU was found on the sleeve cuff of doctors' white coats (Burden et al, 2011) and 51 CFU/25 cm 2 C. difficile spores were recovered from bed linen (Tarrant, Jenkins & Laird, 2018), indicating that the survival rates in vivo could be lower. In vitro studies often use purified cultures of microorganisms without organic soiling which may not reflect conditions where microorganisms are present within organic matter such as bodily fluids (Creamer & Humphreys, 2008).…”
Section: Yeargin Et Al (2016)mentioning
confidence: 99%
“…Badacze z Wielkiej Brytanii zwrócili uwagę na konieczność prania szpitalnej bielizny pościelowej w profesjonalnych pralniach z zastosowaniem dużej ilości detergentów i bardzo wysokiej temperatury. Pranie w pralniach do tego nieprzystosowanych sprzyja przetrwaniu spor, co może wpłynąć na przeniesienie ich na innych pacjentów [11].…”
Section: Wyniki Przegląduunclassified